(untitled) (International Seven Journal of Multidisciplinary, 2021)
Administrative standardization is increasingly recognized as a key driver for improving operational efficiency in small and medium-sized enterprises (SMEs). By implementing standardized procedures and process frameworks, SMEs can enhance productivity, reduce operational costs, and achieve greater scalability. This case study explores the impact of administrative standardization on SME performance, highlighting empirical evidence of process optimization, cost savings, and scalable growth. The findings demonstrate that structured administrative practices foster operational consistency, facilitate decision-making, and support sustainable business development.